2015
DOI: 10.4103/0976-9668.149096
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of DNA damage in Type 2 diabetes mellitus patients with and without peripheral neuropathy: A study in South Indian population

Abstract: Background:The increasing incidence of Type 2 diabetes mellitus globally has collaterally increased the incidence of diabetes-associated complications such as neuropathy. Oxidative stress induced DNA damage is one of the mechanisms implicated in the pathogenesis of diabetic complications. Here we aimed to evaluate the extent of DNA damage in diabetes patients with and without clinical neuropathy using the Cytokinesis Block Micronucleus Cytome assay, in a group of South Indian population.Materials and Methods:T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Nevertheless, our study quite clearly indicated that the frequency of both CTAs and CSAs depends on the duration of the disease, not the type of diabetes. Interestingly, the same type of association has been reported in one CA [ 28 ] and several MN studies in T2DM patients [ 33 , 34 , 35 ]. Conversely, other studies failed to find a correlation between the frequency of MN and disease duration in T2DM [ 36 , 37 ].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Nevertheless, our study quite clearly indicated that the frequency of both CTAs and CSAs depends on the duration of the disease, not the type of diabetes. Interestingly, the same type of association has been reported in one CA [ 28 ] and several MN studies in T2DM patients [ 33 , 34 , 35 ]. Conversely, other studies failed to find a correlation between the frequency of MN and disease duration in T2DM [ 36 , 37 ].…”
Section: Discussionsupporting
confidence: 73%
“…Some authors revealed increased CAs or MN levels in patients with diabetic neuropathy [ 30 , 34 ] or nephropathy [ 33 ]. We did not find any association between the frequency of CAs and diabetes complications, but our sample size was small and, consequently, the statistical power of such analysis was quite low.…”
Section: Discussionmentioning
confidence: 99%
“…No genetic variants were evaluated in this study. The data demonstrated that the frequency of DNA damage was significantly higher in the T2D patients with DPN than in the controls [ 59 ]. Stoian et al conducted a study in the University Center of Tırgu Mures, Romania.…”
Section: Genetic Variants Of Dpn In Different Ethnic Populationsmentioning
confidence: 99%